ダイ 23 ジ エットウ タイ カイヨウ セイブツ カンソク BIOMASS ケイカク ホウコク 1982 - 福地, 光男; フクチ, ミツオ; 谷村, 篤; タニムラ, アツシ; 大塚, 英明; オオツカ, ヒデアキ; 星合, 孝男; ホシアイ, タカオ; Fukuchi, Mitsuo; Tanimura, Atsushi; Ohtsuka, Hideaki; Hoshiai, Takao (1985)
P(論文) 第23次日本南極地域観測隊は, 3年次にわたる研究である「南極沿岸生態系における生物生産の基礎研究」の初年度の観測を担当した。この研究計画は国際共同研究計画"Biological Investigations of Marine Antarctic Systems and Stocks (BIOMASS計画)"の一翼を担うものとして立案されたものであり, 沿岸生態系の主要構成要素についての基本的情報を得ることを目的とした。このため第23次から第25次観測までの間, 海洋生物担当隊員がそれぞれ各3名越冬することとなった。第23次観測隊では特に動物プランクトン, マイクロネクトンの季節変動調査に重点をおいたが, 併せて海洋環境条件の季節変化も調査した。その他ice algaeの生態調査やアデリーペンギン個体数調査も行った。1982年1月から1983年1月の間, 昭和基地周辺の沿岸定着氷上に5観測点を設け, 海洋観測とプランクトン採集を実施した。この周年観測のために, 雪上車, 観測用カブースそり, ウインチなどを用意し, 設営面の充実をも図った。ここでは第23次観測隊の準備状況から観測実施状況を報告する。 The Japanese Antarctic Research Expedition (JARE) planned a three-year programme of shore-based research, "Marine biological production in the Antarctic coastal ecosystem", between 1982 (JARE-23) and 1984 (JARE-25). This research programme was a part of the international "Biological Investigations of Marine Antarctic Systems and Stocks (BIOMASS)" programme. The JARE-23 was the first year of the three-year programme and three marine biologists wintered at Syowa Station. Routine observations of oceanographic conditions and plankton samplings were carried out at five stations on the fast-ice near Syowa Station for a period of 13 months between January 1982 and January 1983. During this period emphasis was put on the ecological studies of zooplankton and micronekton. In addition, an ecological study on ice algae and the population census of the Adelie penguin were also made. departmental bulletin paper